De arcadas e de grooves: uma análise sobre a poética do violinista Ricardo Herz em “Odeon” - Souza, Ismahel Carvalho de (2023)
This dissertation analyzes the musical poetics of Ricardo Herz, focusing on his interpretation and arrangement of the piece "Odeon" for solo violin. The study is anchored in the Theory of Audiotactile Music, providing insights into Herz's distinctive approach to bowing techniques and groove elements in his music. Utilizing specialized audio analysis software, the research examines Herz's stylistic and interpretive choices, particularly in phrasing, dynamics, articulation, and expressive resources. The interplay between violin language and the essence of Ernesto Nazareth's original composition is also explored. This work expands the understanding of rhythmic and pulsive elements in performance, contributing to a broader comprehension of Herz's musical poetics and the role of audiotactile principles in contemporary musical practices.